Genetic polymorphism of the β-lactoglobuline gene in Friesian Holstein cows - Nury HS; Anggraeni A (Indonesian Center for Animal Research and Development (ICARD), 2014)
Milk protein in dairy cattle consists of casein and whey. Whey in milk of dairy cattle is about 20% with the main component is β-lactoglobulin (7-12%). Polymorphism of the β-lactoglobulin gene affects protein and whey production in milk. Selection at a molecular base to improve whey and protein in milk requires information on genetic diversity of the β-lactoglobulin gene, besides other protein genes. This study was aimed to identify genetic polymorphism of the β-lactoglobulin gene in 88 heads of Friesian Holstein (FH) cows at Cikole Dairy Cattle Breeding and Improvement Station (Cikole DCBIS), Lembang. Genotyping was done using Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) method, and a HaeIII restriction enzyme. Genotype frequency, allele frequency, and heterozygosity value were calculated by Nei method. Hardy-Weinberg equilibrium was calculated by chi-square test. Result showed that the β-lactoglobulin gene in the observed HF cattle was polymorphic, in which there were two alleles (A and B) and three genotypes (AA, AB and BB). Frequencies of the A and B alleles were 0.40 and 0.60 respectively; while those of the AA, AB, and BB genotypes were succesively 0.10; 0.60 and 0.30. Heterozygosity value was obtained for 0.483. The β-lactoglobulin gene was in Hardy - Weinberg equilibrium (χ2cal < χ2table). It is concluded that polymorphic of the β-lactoglobulin gene can be used as an initial information for molecular selection on milk protein composition in FH cows. Key Words: HF Cattle, β-lactoglobuline Gene, Genetic Polymorphism, PCR-RFLP